Neural stages of spoken, written, and signed word processing in beginning second language learners - Leonard, Matthew K.; Ferjan Ramirez, Naja; Torres, Christina; Hatrak, Marla; Mayberry, Rachel I.; Halgren, Eric (Frontiers in Human Neuroscience, 2013)
We combined magnetoencephalography (MEG) and magnetic resonance imaging (MRI) to examine how sensory modality, language type, and language proficiency interact during two fundamental stages of word processing: (1) an early word encoding stage, and (2) a later supramodal lexico-semantic stage. Adult native English speakers who were learning American Sign Language (ASL) performed a semantic task for spoken and written English words, and ASL signs. During the early time window, written words evoked responses in left ventral occipitotemporal cortex, and spoken words in left superior temporal cortex. Signed words evoked activity in right intraparietal sulcus that was marginally greater than for written words. During the later time window, all three types of words showed significant activity in the classical left fronto-temporal language network, the first demonstration of such activity in individuals with so little second language (L2) instruction in sign. In addition, a dissociation between semantic congruity effects and overall MEG response magnitude for ASL responses suggested shallower and more effortful processing, presumably reflecting novice L2 learning. Consistent with previous research on non-dominant language processing in spoken languages, the L2 ASL learners also showed recruitment of right hemisphere and lateral occipital cortex. These results demonstrate that late lexico-semantic processing utilizes a common substrate, independent of modality, and that proficiency effects in sign language are comparable to those in spoken language.